Analisis Kesesuaian Fatwa DSN NO:47/DSN-MUI/II/2005 Pada Penyelesaian Pembiayaan Bermasalah Dengan Akad Murahabah - Budiman, Bayu; Fahlevi, Rizal (At-Tamwil: Journal of Islamic Economics and Finance, 2025)
Problematic financing is one of the major risks faced by Islamic banking institutions. Commonly referred to as non-performing financing, this issue can significantly affect the financial stability and operational performance of the institution. This study aims to identify the factors contributing to problematic financing and to analyze the resolution steps undertaken in murabahah contracts at BNI Syariah KCP Jababeka. The research adopts a qualitative approach using descriptive methods. Data were collected through observation, interviews, and documentation, and analyzed using data reduction, data presentation, and verification techniques. Prior to resolving the problematic financing, the bank first identifies the underlying factors and assesses the customer's collectability status. The bank then implements a series of recovery measures through the R3 process: rescheduling, reconditioning, and restructuring. In the final stage, if collateral execution is deemed necessary, BNI Syariah KCP Jababeka proceeds according to the guidelines outlined in the National Sharia Board Fatwa No. 47/DSN-MUI/II/2005, particularly from the first to the fourth provisions of the fatwa. The findings indicate that the handling of problematic financing at BNI Syariah KCP Jababeka is carried out in a systematic manner and ali  gns with sharia principles. These resolution strategies are expected to serve as a reference for other Islamic financial institutions in managing financing risk more effectively and in compliance with sharia law.